Commercially available Capsaicin supplement fails to enhance time-to-exhaustion during cycling - Langan, S. P.; Grosicki, G. J. (International Journal of Exercise Science, 2020)
This study examined whether a commercially available low-dose (1.2 mg), chewable capsaicin supplement could enhance endurance cycling performance. Thirteen young (8M/5F), recreationally active individuals (age = 24.2 ± 2.9 yrs, body fat = 21.2 ± 6.1%) participated in the study. The study consisted of three visits, beginning with an initial evaluation of cardiorespiratory fitness (37.1 ± 5.5 ml/kg/min). During the second and third study visits, participants completed time-to-exhaustion (TTE) tests on a cycle ergometer at a workload eliciting ~90% VO2max, 45 minutes after ingesting either a 139 kcal capsaicin fruit gummy, or eucaloric placebo. Heart rate and rating of perceived exertion (RPE) were recorded every two minutes throughout the TTE sessions. Time-to-exhaustion was not significantly different (p> 0.05; d= 0.13) between placebo (487.8 ± 187.7 sec) and capsaicin (517.5 ± 258.4 sec) trials. Furthermore, heart rate responses and ratings of perceived exertion were similar (p> 0.05) between trials. These findings suggest that pre-exercise ingestion of a commercially available low-dose (1.2 mg), chewable capsaicin supplement fails to provide ergogenic benefits for time-to-exhaustion during cycling exercise. Higher doses may be necessary to elicit the performance-enhancing benefits observed during alternative exercise modalities (i.e., running) of comparable intensity.